GSM CONTROLLED SECURITY AUTOMATION AND BURGLAR TRAP - M.Prabu , S. Nishanth , S.V.Aakash , K.Vishwa Dev (International Journal of Advanced Science and Technology, 2020)
Secure homes provide maximum trust and confidence to an individual. Implementation of security system to residential areas provide much more security. The automation system provides with Arduino ultrasonic sensor based security framework utilizes movement sensor based security framework distinguishes any trespassing that happens in the scope of the movement sensor and makes a call to the owner and alarms. The inclusion of servo door locking system which traps the burglar inside the room.